Poverty alleviation strategies among non-teaching staff of university of inadan (2000)
The major objective of this study was to investigate the coping mechanism of the non-academic staff, University of Ibadan. Information was obtained from the field of by means of well-structured questionnaires from 103 respondent. Majority of the respondents was found to be within the age of 40 and 49. In term of educational level, it was discovered that many of the respondents has formal education about 97 percent. The average household size was 6 person. To be able to cope with poverty, it was discovered that the poor households adopt certain strategies such as engaging in farming, in order business activities to generate additional income, in animal husbandry, buy food on credit at their place of work, buy secondhand cloths or stopped buying entirely and given old cloths to children, finally reduce food consumption among members by eating once or twice in a day. The most adopted strategy is their involvement in multiple income generating activities